The Diamond Hunters - Smith W. Wilbur (Macmillan Guided Readers)
The Van Der Byl Diamond Company, willed by its founder to his son Benedict, turns out to be a bequest of hatred. `Destroy Johnny` is the old man`s implacable message. And so, consumed with envy for his own foster-brother, Benedict sets out in ruthless pursuit of this goal - and Johnny is plunged into a maelstrom of greed, vengeance and murder.